Commercial banks’ profitability and portfolio management in Ghana - Lekwauwa, Nnenne; Bans-Akutey, Anita (goodwood publishing, 2022)
Purpose: The primary goal of the research was to assess the relationship between Ghanaian commercial banks' profitability and portfolio management. Research methodology: All nine of the Ghana Stock Exchange (GSE)'s listed banks were included in the population of this descriptive study. All nine banks were sampled. This study only considered data from financial statements and bank reports covering the five-year period between 2016 and 2021. Results: Results showed that asset investment has a positive effect on the financial performance of commercial banks in Ghana. Additionally, a positive effect of the loan portfolio on the commercial banks’ financial performance was found. It was finally discovered that asset investment affects the banks’ financial performance in a significantly positive way. Limitations: The study was limited to nine banks listed on the GSE. Contribution: It was concluded that when there is a good loan portfolio management policy, banks perform well and are profitable. Consequently, it is advised that top management and other stakeholders play a crucial role in achieving strategic goals by championing best practices in portfolio management and evaluating the sufficiency of effective portfolio management factors in an unbiased manner.